(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The value of treating ground water and surface water as a common tool is becoming increasingly evident as the Nation’s worries about water quality and the climate grow. Issues related to the supply of water, water safety and water depletion are regularly recorded. For all of these concerns the relationship between groundwater and surface water has been shown to be a significant concern. Contaminated aquifers which can drain groundwater into soil, for example, can contribute to long lasting surface water runoff on the other side, groundwater may be a significant source of pollution for water. Surface water is typically hydraulically associated with surface water, but it is challenging to track, quantify and generally neglect the correlations of water and policy management considerations. The relationship of groundwater and surface water is influenced by multiple natural cycles and human activities. The aim of this study is to address our existing understanding and capacity to identify certain processes and practices, as well as limitations.